2001
DOI: 10.1017/s0022112001004232
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated diffusion in the centre of a vortex

Abstract: The spiral wind-up and diffusive decay of a passive scalar in circular streamlines is considered. An accelerated diffusion mechanism operates to destroy scalar fluctuations on a time scale of order P 1/3 times the turn-over time, where P is a Péclet number. The mechanism relies on differential rotation, that is, a non-zero gradient of angular velocity. However if the flow is smooth, the gradient of angular velocity necessarily vanishes at the centre of the streamlines, and the time scale becomes greater. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 34 publications
4
67
0
Order By: Relevance
“…The inner vortex core featuring solid-body rotation is surrounded by a zone where velocities decrease with distance from the center. The decrease of velocity implies high strain rates, leading to accelerated mixing [29,30] and thereby to a supply of heat and radicals to the unburned gas.…”
Section: Helical Flame Zonementioning
confidence: 99%
“…The inner vortex core featuring solid-body rotation is surrounded by a zone where velocities decrease with distance from the center. The decrease of velocity implies high strain rates, leading to accelerated mixing [29,30] and thereby to a supply of heat and radicals to the unburned gas.…”
Section: Helical Flame Zonementioning
confidence: 99%
“…The flow field of the vortex wraps up the passive scalar to form a spiral structure, leading to the diffusive decay of scalar fluctuations in the vicinity of the vortex. Several time scales are involved: in particular there is an enhanced shear-diffusion time scale for the destruction of scalar fluctuations on given closed streamlines (Moffatt & Kamkar 1983;Rhines & Young 1983;Bajer, Bassom & Gilbert 2001). The spiral distribution of the passive scalar also has a fractal nature, with a non-trivial box-counting dimension which can determine spectral power laws and anomalous diffusion properties (for example , Gilbert 1988;Vassilicos 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The result is a decay rate proportional to κ 3/8 . In a natural way, this is larger than the O(κ 1/2 ) decay rate achieved for time-independent flows with extrema, but smaller than the O(κ 1/3 ) found for monotonic velocity profiles [23,24]. Of course, the latter cannot be continuous in periodic domains.…”
Section: Discussionmentioning
confidence: 77%
“…by a number of authors [23][24][25] who found that the concentration decreases to zero very rapidly outside narrow regions around the velocity extrema. The width of these regions then scales with the diffusivity κ like κ 1/4 , leading to a decay rate proportional to κ 1/2 .…”
Section: Introductionmentioning
confidence: 99%